A Novel Architecture for the Realization of an Internet of Things- Enabled ECG Signal Quality Aware using Empirical Mode Decomposition for Healthcare System - Chukka, Ramesh Babu; Kumar, Chennupati Sumanth (International Journal of Engineering and Technology, 2018)
From the last few years, physical challenges in the field of ECG Framework are de-noising the signal and the improvement of battery-life of the system. This proposed paper consists of the 3 modules: 1) Denoising the ECG signal using decomposition techniques; 2) Implementing the Automatic Signal Quality-Aware algorithm and 3) Transmission of acceptable signal of ECG as a trigger to the IoT-Enabled ECG Telemetry system for achieving energy efficiency. Here in this paper the decomposition technique, namely EMD is implemented and its performance where compared and analyzed with the DWT technique using matlab by calculating correlation and SNR Thus the proposed paper has great potential in meeting up the two main challenges, namely denoising the ECG signal and improving the energy efficiency of the device.